Comparison of the effectiveness of whole-brain radiotherapy plus temozolomide versus whole-brain radiotherapy in treating brain metastases based on a systematic review of randomized controlled trials. Issue 1 (January 2016) - Bai, Gui-Rong; An, Jin-Bing; Chu, Yang; Wang, Xiang-Yang; Li, Shu-Ming; Yan, Kai-Jing; Lü, Fu-Rong; Gu, Ning; Griffin, Amanda N.; Sun, Bin-Yuan; Li, Wei; Wang, Guo-Cheng; et al.
Abstract : Temozolomide (TMZ) combination with whole-brain radiotherapy (WBRT) has been tested by many randomized controlled trials in the treatment of brain metastases (BMs) in China and other countries. We performed an up-to-date meta-analysis to determine (i) the log odds ratios (LORs) of objective response (ORR) and adverse effects (AEs) for all-grade, and (ii) the T value of mean overall survival in patients with BMs treated with WBRT combined with TMZ versus WBRT alone. PubMed, Chinese National Knowledge Infrastructure, and WanFang Data were searched for articles published up to 28 January 2015. Eligible studies were selected according to the PRISMA statement. ORR, AEs, and 95% confidence intervals were calculated using random-effects models. Eighteen studies were included in our analysis. A total of 1028 participants were enrolled. Summary LORs of ORR were 1.0239 ( P <0.0001) on comparing WBRT plus TMZ with WBRT ORR ( n =17). The overall mean difference of mean overall survival ( n =17) between TMZ plus WBRT and WBRT was 2.2505 weeks ( P =0.02185). There was a significant difference between WBRT plus TMZ and WBRT alone with a LOR of AEs for all-grade of (i) 0.923 for gastrointestinal toxicity and (ii) 0.7978 for myelosuppression. Sensitivity analysis and subgroup analysis were also performed. The 18 eligible randomized controlled trials demonstrated that the combination of WBRT and TMZ significantly improves the ORR and is statistically insignificant in prolonging the survival of patients with BMs. In addition, an increase in the incidence of gastrointestinal toxicity and myelosuppression was significant for all-grade. Abstract : Supplemental Digital Content is available in the text.